2005
DOI: 10.1007/s11064-005-2678-0
|View full text |Cite
|
Sign up to set email alerts
|

In vivo Quinolinic Acid Increases Synaptosomal Glutamate Release in Rats: Reversal by Guanosine

Abstract: Glutamate, the main excitatory neurotransmitter in the mammalian central nervous system (CNS), plays important role in brain physiological and pathological events. Quinolinic acid (QA) is a glutamatergic agent that induces seizures and is involved in the etiology of epilepsy. Guanine-based purines (GBPs) (guanosine and GMP) have been shown to exert neuroprotective effects against glutamatergic excitotoxic events. In this study, the influence of QA and GBPs on synaptosomal glutamate release and uptake in rats w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 34 publications
(37 reference statements)
0
46
0
2
Order By: Relevance
“…Of note, glutamate release from astrocytes has access to extrasynaptic neuronal glutamate receptors that when activated can lead to decreased BDNF and increased excitotoxicity (Hardingham et al, 2002;Hardingham and Bading, 2010). In addition, inflammatory cytokine-induced activation of IDO can lead to the production of quinolinic acid by microglia that can bind to glutamate (N-methyl-Daspartate (NMDA)) receptors while also stimulating glutamate release from astrocytes (Tavares et al, 2002(Tavares et al, , 2005Schwarcz et al, 2012). Indeed, in studies from postmortem tissue of presumably depressed suicide victims, activated microglia expressing quinolinic acid have been described in the anterior cingulate cortex (Steiner et al, 2011).…”
Section: Inflammation Effects On Neurotransmitter Metabolismmentioning
confidence: 99%
“…Of note, glutamate release from astrocytes has access to extrasynaptic neuronal glutamate receptors that when activated can lead to decreased BDNF and increased excitotoxicity (Hardingham et al, 2002;Hardingham and Bading, 2010). In addition, inflammatory cytokine-induced activation of IDO can lead to the production of quinolinic acid by microglia that can bind to glutamate (N-methyl-Daspartate (NMDA)) receptors while also stimulating glutamate release from astrocytes (Tavares et al, 2002(Tavares et al, , 2005Schwarcz et al, 2012). Indeed, in studies from postmortem tissue of presumably depressed suicide victims, activated microglia expressing quinolinic acid have been described in the anterior cingulate cortex (Steiner et al, 2011).…”
Section: Inflammation Effects On Neurotransmitter Metabolismmentioning
confidence: 99%
“…Guo may bind to its putative (uncloned) G-protein-coupled receptors in the brain [50,51]. Guanosine levels increased after PTZ-induced seizures [372], and Guo exerts a protective effect on quinolinic acid (QA)-induced seizures [60-62, 368, 373-377] (Table 4) and -dendrotoxin-induced seizures [371] likely by stimulation of astrocytic glutamate uptake [89,373,377,378]. It has been demonstrated that GMP-and GTP-induced decreases in seizures may be related to their conversion to Guo [89,368,375].…”
Section: Non-adenosine Nucleosides: Uridine Guanosine and Inosinementioning
confidence: 99%
“…It could be therefore that the increase in gamma oscillations induced by MK-801 (Pinault, 2008) is related to non-NMDA receptors activation. In this sense, whereas the MK-801 dose we used (0.5 mg/kg) was unable to promote higher gamma activity, the co-treatment with QA, which can also influence release and uptake of glutamate (de Oliveira et al, 2004;Tavares et al, 2002Tavares et al, , 2005, could have synergistically increased the activation of non-NMDA receptors, leading to the observed increase in gamma oscillations. In fact, Pinault (2008) described that the appearance of gamma oscillations with MK-801 treatment was accompanied by ataxic behavior; as we did not observe ataxic behavior under our treatment protocol, this suggests that the effective dose of MK-801 reaching the brain was in fact higher in Pinault (2008) study than in the present work.…”
Section: Discussionmentioning
confidence: 95%
“…It has been suggested that astrocytes are crucially involved, since guanosine was shown to stimulate glutamate uptake by astrocytes (Frizzo et al, , 2002(Frizzo et al, , 2003, which is the main mechanism of glutamate removal from the synaptic cleft (Danbolt, 2001;Beart and O'Shea, 2007). In addition, recent works have shown that QA decreases glutamate uptake in vivo and that this effect is reverted by guanosine when successfully acting as anticonvulsant (de Oliveira et al, 2004;Tavares et al, 2002Tavares et al, , 2005. Taken together, there is strong evidence that the antiglutamatergic action of guanosine occurs in a fundamentally different way than MK-801, which would explain the different electrophysiological results observed here in the network (EEG) level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation